The China -Pakistan Economic Corridor: A Critical Analysis of Gulf- Crisis - AZEEZ, Ismail Adaramola Abdul (Journal of Tourism Economics and Policy, 2023)
The Chino-Pakistan Economic Corridor (CPEC), initialed in 2013, is among China’s biggest foreign policy and investment commitments. It links China's Xinjiang Province with the Arabian Sea overland through Pakistan by three major new transportation corridors, supplemented by new power plants fueled by both renewables and coal, and establishing new industrial parks and trade zones. The project could transform Pakistan, but it also has clear implications for the Gulf States and after the outbreak of the Qatar crisis in 2017, CPEC became an arena of competition for the Gulf States. China-Pakistan Economic Corridor (CPEC) is a part of a strategic geopolitical move that promises not only augment the strategic position of Pakistan but also unleashing socio-economic potentials of Qatar and China. The research is an effort to highlights the interest of china and Pakistan regarding CPEC. Keeping in view the geo-strategic location of Gwadar port It also provides an insight into the challenges regarding CPEC It also endorses why Qatar is keenly interested to join the CPEC and how its involvement boosts its economy? The proposed research is based on descriptive and analytical research methods where the researcher consults primary and secondary sources to support their argument. So, in this way, the results suggest that strategically CPEC would provide a supported system to Qatar to transform its move into a truly interconnected world. This project can potentially strengthen the macroeconomic cooperation connectivity peace, and growth among different countries through trade and business opportunities which will further generate revenues for Qatar.